2009
DOI: 10.1007/s11695-009-9919-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Laparoscopic Sleeve Gastrectomy on Iron Indices: 1 Year Follow-Up

Abstract: LSG is an effective procedure for the treatment of morbid obesity and its associated inflammatory state. One year after surgery, development of iron deficiency was insignificant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 26 publications
5
56
2
Order By: Relevance
“…The reduction of the stomach promotes reduced food intake and reduced parietal cells, resulting in decreased production of hydrochloric acid, which is important in the absorption of iron. There are vitamin B12, folic acid and iron deficiencies in 4.9% of patients, and anemia in 4.9% 32,33 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…The reduction of the stomach promotes reduced food intake and reduced parietal cells, resulting in decreased production of hydrochloric acid, which is important in the absorption of iron. There are vitamin B12, folic acid and iron deficiencies in 4.9% of patients, and anemia in 4.9% 32,33 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…According to the results of the reviewed studies (Table 3), pre-operative folate deficiency has been estimated to exist in up to 54% of the subjects, whereas recent studies from the USA support that this prevalence is much lower, about 0-6% [34][35][36]. Five studies found that the prevalence of follic acid deficiency one year after BS ranges between 0% and 15% [17,19,25,26,37] . their studies that folate deficiency occurred in 15% and 9,8% of their patients respectively, one year after VSG [25,37].…”
Section: Methodsmentioning
confidence: 99%
“…Five studies found that the prevalence of follic acid deficiency one year after BS ranges between 0% and 15% [17,19,25,26,37] . their studies that folate deficiency occurred in 15% and 9,8% of their patients respectively, one year after VSG [25,37].…”
Section: Methodsmentioning
confidence: 99%
“…Hakeam et al found a low incidence of iron defi ciency (4.9 %) and of anemia (1.6 %) 12 months after surgery [ 43 ]. After 1 year, the impact of this bariatric surgery on iron indices was negligible.…”
Section: Nutrient Defi Ciencies After Lsgmentioning
confidence: 98%
“…Therefore, patients undergoing LSG might require more than the RDA of folic acid to maintain normal folate levels. This could be attributed to the diet changes after surgery [ 43 ]. Also, more attention has to be directed to folic acid and vitamin B12 in females planning to get pregnant after LSG, as folic acid and vitamin B12 defi ciency during pregnancy in general population has been linked to the increased risk of neonatal neural tube defects.…”
Section: Nutrient Defi Ciencies After Lsgmentioning
confidence: 99%